1978
DOI: 10.1254/jjp.28.545
|View full text |Cite
|
Sign up to set email alerts
|

On the Histamine Receptor of the Canine Myocardium and Coronary Vasculature

Abstract: Abstract-To indentify the histamine-receptors in the canine myocardium, experiments were performed in the canine heart-lung preparation supported by a donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The response of coronary hemodynamics to Hi-receptor activation in man, at the histamine concentration used in our study, was characterized by a significant decrease in CVR in the majority of patients. Since there was no net change in the determinants of MVO2, this decrease in CVR could to some extent be attributed to the stimulation of vasodilating Hx-receptors present in the small resistance coronary arteries, in agreement with reports of H 1-receptor-induced vasodilatation without changes in MVO 2 [9,10]. We cannot exclude, however, that other mediators released by histamine may be responsible for this effect.…”
Section: Discussionsupporting
confidence: 90%
“…The response of coronary hemodynamics to Hi-receptor activation in man, at the histamine concentration used in our study, was characterized by a significant decrease in CVR in the majority of patients. Since there was no net change in the determinants of MVO2, this decrease in CVR could to some extent be attributed to the stimulation of vasodilating Hx-receptors present in the small resistance coronary arteries, in agreement with reports of H 1-receptor-induced vasodilatation without changes in MVO 2 [9,10]. We cannot exclude, however, that other mediators released by histamine may be responsible for this effect.…”
Section: Discussionsupporting
confidence: 90%
“…In relatively simple and controlled systems such as the blood-perfused right atrium [9] or the heart-lung preparation [8,10], histamine was found to produce positive inotropic responses, either partially or totally blocked by H 1 or a combination of H1 and H2 antagonists. However, it should be noted that in all cases the amine produced simultaneous positive chronotropic effects and that, in general, susceptibility to blockade by the antagonists tested was similar for inotropic and chronotropic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although such responses were not systematically evaluated in the present study, preliminary experiments in unpaced preparations showed that the threshold inotropic dose of 0.1 mg already produced a substantial increase in heart rate. By the same token, histamine elicits coronary dilatation in the dog, presumably through stimulation of H 1 and H 2 receptors [10,14,23]. Evaluation of this effect was not attempted, both because it has already been adequately characterized and in order not to complicate more an already complex experimental preparation.…”
Section: Effect8 Of Hi8tamine On 180volumic Pressure Before and Aftermentioning
confidence: 99%